GROWTH AND YIELD OF MUNGBEAN (VIGNA RADIATA L.) IN RESPONSE TO THE APPLICATION OF SULPHUR AND BORON UNDER RAINFED CONDITIONS - MOHIT SINGH,; PAWAN SIROTHIA,; MOHAMMAD AMIN BHAT,; PAWAN TIWARI,; ANURAG NAMDEO, (The Bioscan, 2015)
A field experiment was conducted during the kharif season of 2013–14 to study the effect of sulphur (S) and boron (S) on growth and yield of mungbean (Vigna radiata L.). The treatment combinations comprised four levels of sulphur (0, 10, 20 and 30 kg ha -1 ) and three levels of boron (0, 100 and 200 ppm) in randomized block design with three replications. The maximum plant height (68.90 cm) and maximum number of leaves (35.75) were recorded significantly higher over control at 60 DAS with sulphur application at the rate of 30kg ha -1 . Likewise, the maximum plant height (67.57 cm) and maximum number of leaves (34.51) were recorded significantly higher over control at 60 DAS with boron application at the rate of 200 ppm. However, data regarding number of branches was found non significant with different levels of sulphur and boron. Moreover, both seed and stover yield of mungbean was significantly higher and peak values were 502.7, 490.6 and 1504.5, 1437.1 kg ha -1 , respectively at sulphur level of 30kg ha -1 and boron level of 200 ppm. Similar trend was observed in case of number of root nodules. Hence, sulphur and boron are important nutrients for better production and productivity of mungbean.